SOME CHALLENGES AND POSSIBILITIES FOR EDUCATION OF HUMAN AND ETHICAL VALUES THAT CONTEMPLATE DIVERSITY IN BRAZILIAN UNIVERSITY EDUCATION - Antonio Casagrande, Cledes; Regina Quaresma da Silva, Denise (Revista Gênero e Interdisciplinaridade, 2021)
This theoretical study, with a qualitative approach, proposes a reflection on education for diversity in Brazilian university education. We will initially seek an approach to the theme of diversity, especially through the historical conceptual bias. Then, we will discuss some assumptions that can support a proposal for training for diversity from the perspective of the university. We conclude by presenting some challenges and possibilities to the university’s training action in an attempt to dialogue about other elements, skills and competences necessary for the training of young people and adults for an education of human and ethical values ​​that contemplate diversity, understanding the social function of the university as the institution responsible for training the subjects fully for the exercise of citizenship and for the world of work through teaching, research and extension actions.